Reshaping of soil properties and microbial community by the conversion from non-grain cultivated land to paddy field - Li, Xuqing; Chen, Han; Wang, Xiao; Ali, Qurban; Lv, Luqiong; Zhou, Tiefeng; Ijaz, Munazza; Ahmed, Temoor; Yan, Jianli; Li, Bin (Frontiers in Microbiology, 2025)
BackgroundIn order to ensure food security, China is actively carrying out conversion of nongrain cultivated land to paddy field. Therefore, it is very necessary to investigate the influence of this conversion on soil health, which has been well known to play an important role in crop growth.MethodsA combined analysis of soil physicochemical properties, bacterial community structure, and metabolite was conducted on 72 soil samples, which were collected in this study from the converted paddy fields and the corresponding non-grain cultivated lands including loquat garden, mulberry field, blueberry garden, vineyard, bamboo garden and nursery stock base.ResultsIn this study, conversion of non-grain cultivated land to paddy field significantly influenced physicochemical properties, bacterial community structure, and metabolite of root-zone soil with 8.08–43.85%, 8.90–64.14%, 24.98–91.97%, 38.74–92.52%, and 5.12–32.99% reduction in soil organic matter content (SOM), alkaline hydrolysis nitrogen (AHN), available phosphorus (AP), available potassium (AK), and microbial biomass carbon (MBC), respectively; 0.81–3.08 fold, 1.26–21.50 fold, and 4.29–14.54 fold increase in relative abundance (RAs) of Chloroflexi, Desulfobacterota, and Nitrospirota, respectively; and 2,204 differentially expressed metabolite (DEMs) belonging to amino acids and derivatives, benzene and substituted derivatives, flavonoids, lipids, organic acids, terpenoids. Furthermore, correlation analysis indicated that these DEMs were significantly correlated with some specific bacteria, thereby helping in coordinating the root-zone soil community during conversion, while these bacteria were also correlated with soil properties.ConclusionOverall, this study highlights the importance of bacterial communities during conversion of non-grain cultivated land to paddy field, which provided a scientific basis and supporting evidence for the renovation of non-grain cultivated land.